Complex Tax Incentives - An Experimental Investigation - Johannes Abeler; Simon Jäger (Center for Economic Studies and ifo Institute (CESifo), 2013)
How does tax complexity affect people's reaction to tax changes? To answer this question, we conduct an experiment in which subjects work for a piece rate and face taxes. One treatment features a simple, the other a complex tax system. The payoff-maximizing effort level and the incentives around this optimum are, however, identical across treatments. We introduce the same sequence of additional taxes in both treatments. Subjects in the complex treatment underreact to new taxes; some ignore new taxes entirely. Contrary to predictions from models of rational inattention, subjects are equally likely to ignore large or small incentive changes.
Keywords: C91; D03; H31; J22; 330; complexity; taxation; attention; salience; laboratory experiment